2014
DOI: 10.1146/annurev-neuro-071013-014300
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E in Alzheimer's Disease: An Update

Abstract: The vast majority of Alzheimer's disease (AD) cases are late onset (LOAD), which is genetically complex with heritability estimates up to 80%. Apolipoprotein E (APOE) has been irrefutably recognized as the major genetic risk factor, with semidominant inheritance, for LOAD. Although the mechanisms that underlie the pathogenic nature of APOE in AD are still not completely understood, emerging data suggest that APOE contributes to AD pathogenesis through both amyloid-β (Aβ)-dependent and Aβ-independent pathways. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
296
0
9

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 366 publications
(311 citation statements)
references
References 152 publications
6
296
0
9
Order By: Relevance
“…Among these, ApoE is known to participate in Aβ production, aggregation, and clearance in an isoform-dependent manner 83,84 . Cholesterol levels in the brain can affect Aβ synthesis, clearance and neurotoxicity.…”
mentioning
confidence: 99%
“…Among these, ApoE is known to participate in Aβ production, aggregation, and clearance in an isoform-dependent manner 83,84 . Cholesterol levels in the brain can affect Aβ synthesis, clearance and neurotoxicity.…”
mentioning
confidence: 99%
“…5E,F). Apolipoprotein E (ApoE) protein has been demonstrated to play important roles in Aβ production, aggregation, and clearance (Yu et al ., 2014). Lipoprotein receptor‐related protein 1 (LRP1), an ApoE‐binding protein, has also been identified to be involved in all these processes, contributing to the pathogenesis of AD (Harris‐White & Frautschy, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…74,75 One of these studies included a discovery microarray approach that identified a number of proteins that are differentially expressed in such subjects, including APP binding protein and regulators of apoptosis, trafficking, cytoskeletal structure, and cell-cycle proteins. 74 Work by Perez-Nievas et al 75 showed more fibrillar and oligomer-positive Ab plaques, increased p-tau oligomers, and glial activation in demented compared with nondemented subjects with underlying AD pathology. In another study, low molecular weight SDSstable Ab oligomers were associated with the postsynaptic density in patients with Alzheimer dementia but not in nondemented HPCs.…”
Section: Discussionmentioning
confidence: 99%